Justice cascade : how human rights prosecutions are changing world politics how human rights prosecutions are changing world politics - Sikkink, Kathryn, 1955- (New York : W. W. Norton & Co., 2011)
Over the past three decades, hundreds of government officials have gone from being immune to any accountability for their human rights violations to being the subjects of highly publicized trials in Latin America, Europe, and Africa, resulting in enormous media attention and severe consequences. Here, renowned scholar Kathryn Sikkink brings to light the groundbreaking emergence of these human rights trials as a modern political tool, one that is changing the face of global politics as we know it. Drawing on personal experience and extensive research, Sikkink explores the building of this movement toward justice, from its roots in Nuremberg to the watershed trials in Greece and Argentina. She shows how the foundations for the stunning, public indictments of Slobodan Milosevic and Augusto Pinochet were laid by the long, tireless activism of civilians, many of whose own families had been destroyed, and whose fight for justice sometimes came at the risk of their own lives and careers. She also illustrates what effect the justice cascade has had on democracy, conflict, and repression, and what it means for leaders and citizens everywhere, including the policymakers behind our own "war on terror."--From publisher description.
Part I: Creating individual accountability. Navigating without a map : human rights trials in Southern Europe ; Argentina : from pariah state to global protagonist -- Part II: Spreading ideas about individual accountability. Interlude: How and why does the Argentine experience spread? ; The streams of the justice cascade -- Part III: Do human rights prosecutions make a difference? The effects of human rights prosecutions in Latin America ; Global deterrence and human rights prosecutions ; Is the United States immune to the justice cascade? -- Part IV: Conclusions. Policy, theory, and the justice cascade.
Includes bibliographical references (p. 307-322) and index.
Keywords: Crimes against humanity; Criminal liability (International law); Prosecution -- International cooperation; Criminal justice, Administration of -- International cooperation; International criminal courts; World politics -- 1989-; Crimes against humanity; Administration of criminal justice -- International cooperation; World politics -- 1991-